Malnutrition and Developmental Delay Presenting as Complications of Late Onset Hirschprung’s disease : A Case Report - Pujiati, Pujiati; Raharjo, Rudi Yuwono; Ovaditya, Shafira Zahra (Diponegoro International Medical Journal, 2023)
Background: Hirschsprung’s Disease is a congenital disorder characterized by the absence of ganglionic cells in the colon, causing loss of peristaltic movement in the bowel. Most cases are diagnosed before the age of one and marked by the delayed passage of meconium, vomiting, and distended abdomen. Here, we present a case of a 2-year-old boy with an atypical presentation of malnutrition and developmental delay as a complication of Hirschsprung’s Disease. Case Presentation: A 2-year-old boy who presented with abdominal distention and chronic constipation was referred to our hospital. Past personal history revealed that he frequently suffered from the symptoms but was previously diagnosed with regular constipation and only consumed symptomatic medication. On admission, his vital signs were all normal, but his appearance was pale and weak. Growth and developmental screening showed poor growth status and developmental delay in all four domains. From the physical examination, gross abdominal distention was found and the rectal examination demonstrated a tight anal sphincter, empty rectal vault, and a green-colored stool with no forceful expulsion. Radiologic and histopathological findings suggested Hirschsprung’s disease. Conclusion: Chronic abdominal distention followed by malnutrition and developmental delay can present as a complication of hirschsprung’s diseasein older children. Due to these subtle signs and symptoms, a thorough examination and proper diagnostic algorithm are